Whole milk compared with reduced-fat milk and childhood overweight: a systematic review and meta-analysis. Issue 2 (18th December 2019) - Vanderhout, Shelley M; Aglipay, Mary; Torabi, Nazi; Jüni, Peter; da Costa, Bruno R; Birken, Catherine S; O'Connor, Deborah L; Thorpe, Kevin E; Maguire, Jonathon L
ABSTRACT: Background: The majority of children in North America consume cow-milk daily. Children aged >2 y are recommended to consume reduced-fat (0.1–2%) cow-milk to lower the risk of obesity. Objectives: To evaluate the relation between cow-milk fat consumption and adiposity in children aged 1–18 y. Methods: Embase (Excerpta Medica Database), CINAHL (Cumulative Index to Nursing and Allied Health Literature), MEDLINE, Scopus, and Cochrane Library databases from inception to August 2019 were used. The search included observational and interventional studies of healthy children aged 1–18 y that described the association between cow-milk fat consumption and adiposity. Two reviewers extracted data, using the Newcastle–Ottawa Scale to assess risk of bias. Meta-analysis was conducted using random effects to evaluate the relation between cow-milk fat and risk of overweight or obesity. Adiposity was assessed using BMI z -score (zBMI). Results: Of 5862 reports identified by the search, 28 met the inclusion criteria: 20 were cross-sectional and 8 were prospective cohort. No clinical trials were identified. In 18 studies, higher cow-milk fat consumption was associated with lower child adiposity, and 10 studies did not identify an association. Meta-analysis included 14 of the 28 studies ( n = 20, 897) that measured the proportion of children who consumed whole milk compared with reduced-fat milk and direct measures of overweight or obesity. Among children who consumed whole (3.25% fat) compared with reduced-fat (0.1–2%) milk, the OR of overweight or obesity was 0.61 (95% CI: 0.52, 0.72; P < 0.0001), but heterogeneity between studies was high ( I 2 = 73.8%). Conclusions: Observational research suggests that higher cow-milk fat intake is associated with lower childhood adiposity. International guidelines that recommend reduced-fat milk for children might not lower the risk of childhood obesity. Randomized trials are needed to determine which cow-milk fat minimizes risk of excess adiposity. This systematic review and meta-analysis was registered with PROSPERO (registration number: CRD42018085075).